The Analysis of Public Policy in Dynamic Urban Models - Oates, W. E.; Howrey, E. P.; Baumol, W. J. (Journal of Political Economy, 1971)
In a process of cumulative city deterioration, dynamic models which explicitly incorporate policy variables may be essential to determine policy measures capable of effecting desired long-run changes. This paper presents some simple dynamic models and explores their implications for policies to achieve various public goals. In particular, the analysis points up the distinction between policies, often quite attractive on the surface, which may in fact promise at best only short-run improvements and those which can alter the values of the parameters which determine the equilibrium characteristics of the city. To illustrate the potential use of such models, the paper also reports some empirical estimates of the parameters of two such models and discusses their policy implications.